Early childhood professionals' perceptions of children's school readiness characteristics in six countries. (2018) - Niklas, Frank; Cohrssen, Caroline; Vidmar, Maša; Segerer, Robin; Schmiedeler, Sandra; Galpin, Rolf; Klemm, Vera Valeska; Kandler, Simone; Tayler, Collette
Highlights: In total, 1198 early years (EY) professionals in six countries were surveyed. EY professionals' perspectives on school readiness characteristics were analysed. Independence, social competencies, and concentration were deemed to be important. Specific precursors of academic achievement were regarded as less important. Ratings differed across occupations, countries, sex, and work experience. Abstract: The opinions of early years educators and primary school teachers regarding the school readiness characteristics (SRC) that best support a child's positive transition to school differ. The aims of our study were to determine key elements of perceived SRC and to identify the priorities of pre-service and in-service early years professionals in six countries: Australia, Austria, Colombia, Germany, Nicaragua, and Slovenia. In total, 1198 early years professionals responded to a survey that investigated perceptions of child school readiness characteristics. Independence, social skills and concentration were reported to be very important. Academic precursors and physical development were reported to be the least important SRC. Findings for the total sample and specific subgroups are presented and discussed.